2001
DOI: 10.1054/bjoc.2000.1540
|View full text |Cite
|
Sign up to set email alerts
|

Pluronic F68 block polymer, a very potent suppressor of carcinogenesis in the colon of rats and mice

Abstract: Polyethylene-glycol (PEG) is a strong inhibitor of colon cancer in rats, and the most potent suppressor of aberrant crypt foci. 9 PEG-like block copolymers were tested in rodents, after an azoxymethane injection. Dietary pluronic F68 led to a 98.6% reduction in the number of aberrant crypt foci in a first rat study ( P < 0.0001). Next 3 studies confirmed this pluronic efficacy in rats and mice. This non-toxic laxative seems roughly 5 times more potent than PEG for chemoprevention. © 2001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…PEG has been shown to reduce both ACF and colon carcinogenesis. 10,14,17,18 Accordingly, we found that ACF were dramatically reduced in rats treated with PEG. In addition, we demonstrated that PEG almost inhibited MDF, since there was only 1 MDF in the rats treated with PEG, a finding that supports the correlation between MDF and carcinogenesis.…”
Section: Discussionmentioning
confidence: 67%
“…PEG has been shown to reduce both ACF and colon carcinogenesis. 10,14,17,18 Accordingly, we found that ACF were dramatically reduced in rats treated with PEG. In addition, we demonstrated that PEG almost inhibited MDF, since there was only 1 MDF in the rats treated with PEG, a finding that supports the correlation between MDF and carcinogenesis.…”
Section: Discussionmentioning
confidence: 67%
“…Poloxamer 407 halved the number of ACF but Pluronic L64 and NP30 had little effect. Poloxamer 181 also had little effect on the ACF number in the rats, as compared to controls (Parnaud et al 2001).…”
Section: Anticarcinogenicitymentioning
confidence: 84%
“…Also, 80% of the rats of the test group survived the 8-week trial period compared to 23% of the control group (Silk and Sigman 1972). Parnaud et al (2001) conducted in vivo studies on the effect of Poloxamer 188 on colon cancer in rats and mice. A total of 158 4-week-old F344 rats and OF1 mice were included in the studies.…”
Section: Anticarcinogenicitymentioning
confidence: 99%
“…5 It has also been used as antiplatelet therapy in coronary angioplasty, 2,44 an antisludging agent in extracorporeal membrane oxygenators, 2,28,49 a soluble bone wax for hemostasis, 47 and as a suppressor of carcinogenesis in a rodent model of colon cancer. 33 The effects of poloxamer on excitable tissues have been mostly protective. Poloxamer 188 has been found to reduce neurological injury in a dog model of hypothermic circulatory arrest, 27 and to reduce tissue injury in a rabbit model of frostbite.…”
Section: Discussionmentioning
confidence: 99%